ZNF8 Orchestrates with Smad3 to Promote Lung Metastasis by Recruiting SMYD3 in Breast Cancer - Wenwen Geng; Junhua An; Ke Dong; Hailu Zhang; Xiuyuan Zhang; Yuchen Liu; Rong Xu; Yifan Liu; Xiaofen Huang; Haiyun Song; Wei Yan; Aihua Sun; et al. (Advanced Science)
Abstract Most deaths in breast cancer patients are attributed to metastasis, and lung metastasis is associated with a particularly poor prognosis; therefore it is imperative to identify potential target for intervention. The transforming growth factor‐β (TGF‐β) pathway plays a vital role in breast cancer metastasis, in which Smad3 is the key mediator and performs specific functions by binding with different cofactors. However, Smad3 cofactors involved in lung metastasis have not yet been identified. This study first establishes the interactome of Smad3 in breast cancer cells and identifies ZNF8 as a novel Smad3 cofactor. Furthermore, the results reveal that ZNF8 is closely associated with breast cancer lung metastasis prognosis, and specifically facilitates TGF‐β pathway‐mediated breast cancer lung metastasis by participating in multiple processes. Mechanistically, ZNF8 binds with Smad3 to enhance the H3K4me3 modification and promote the expression of lung metastasis signature genes by recruiting SMYD3. SMYD3 inhibition by BCI121 effectively prevents ZNF8‐mediated lung metastasis. Overall, the study identifies a novel cofactor of TGF‐β/Smad3 that promotes lung metastasis in breast cancer and introduces potential therapeutic strategies for the early management of breast cancer lung metastasis.